The Correlation Between Nurses Caring Attitudes And The Implementation Of Holistic Nursing Care In Patient Care In The Inpatient - Habib Karim Amrullah; Etlidawati Etlidawati; Jebul Suroso; Suci Ratna Estria (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Caring attitudes form the core of nursing practice, fostering therapeutic relationships and enhancing care quality. Holistic nursing care encompasses patients' physical, psychological, social, and spiritual aspects. The research location was chosen because of the diverse characteristics of the patients. A preliminary study on July 7, 2025, using observation and interviews, found variations in patient perceptions of nurse caring, particularly in communication and emotional support. This study aimed to analyze the relationship between nurses' caring attitudes and the implementation of holistic nursing care among inpatients. It employed a quantitative cross-sectional design with purposive sampling (n=90 respondents based on inclusion criteria). Instruments: CBI-24 and HCQAS-P questionnaires (adapted without modification; validity 0.69–0.78 and 0.446-0.799, p<0.01). Data were analyzed using the Chi-square test (p<0.05). Most respondents were male (58.9%), aged 60 years (42.2%), elementary-educated (41.1%), and private sector workers (95.6%). Caring attitudes were rated high by 73.3%, and holistic nursing care implementation was good by 76.7%. A significant relationship was found (p=0.001). These findings align with prior studies, emphasizing the need for ongoing caring training and hospital policy support in regional hospitals.